How can indigenous research contribute to universal knowledge?: an illustration with research on interpersonal harmony - Leung, Kwok; Wang, Jie; Deng, Hong (Wiley, 2016)
The indigenous perspective can provide a more complete, in‐depth, and accurate account of psychological phenomena for a given culture, but a major issue is that indigenous research tends to be ignored by researchers from other cultures. Chinese researchers who conduct research on indigenous issues may find it hard to publish in major English‐language journals. This paper explores how Chinese indigenous research is able to contribute to universal knowledge. Chinese are characterized by a relational and collectivistic orientation, whereas theories in the West tend to have a self‐focus, primarily due to its individualistic culture. However, most psychological research conducted in the Chinese context is guided by Western theories, which likely results in incomplete understanding of Chinese behavior. A relational perspective can augment Western theories and facilitate the contribution of Chinese indigenous research to new theory development. To illustrate this possibility, this article summarizes current indigenous research on two harmony motives, and shows how such research can contribute to a compelling refinement and extension of social exchange theory.